Growth of Listeria monocytogenes in salmon roe – A kinetic analysis. (January 2016) - Li, Changcheng; Huang, Lihan; Hwang, Cheng-An; Chen, Jinquan
Abstract: The objective of this study was to investigate the growth kinetics of Listeria monocytogenes in unsalted and salted (3%) salmon roe. Growth curves, developed using inoculated samples incubated at constant temperatures between 5 and 30 °C, were analyzed by curve-fitting to the Huang and Baranyi models using the USDA IPMP 2013. The experimental results showed that L. monocytogenes in salted samples exhibited approximately 40% longer lag times than the cells in unsalted samples under the same temperature condition, while the rates of bacterial growth were not affected by the addition of salt. The Ratkowsky square-root (RSR) model, Huang square-root (HSR) model, and an Arrhenius-type model were all shown suitable for evaluating the effect of temperature on specific growth rates. The estimated nominal minimum growth temperature in the RSR model was −0.5 °C, whereas the minimum growth temperature in HSR model was 2.57 °C. The HSR models may be more suitable for describing the temperature effect in salted salmon roe. The lag times of L. monocytogenes were found to change log-linearly with the specific growth rates. The mean h0 in the Baranyi model was 0.742 in unsalted samples and 1.193 in salted samples, and did not appear to change with temperature in a systematic manner. In summary, kinetic models were developed for examining the effect of temperature on growth of L. monocytogenes in unsalted and salted salmon roe samples. The results may be used by the food industry and regulatory agencies to estimate the growth of L. monocytogenes in salmon roe, and to conduct risk assessments of this microorganism. Highlights: Effect of temperature and salt on growth kinetics of L. monocytogenes was investigated. Salt at 3% increased the lag times by 40%, but did not affect growth rates. Kinetic models were developed.